Insulin Overdose - Richard Stair (Association of American Medical Colleges, 2008)
Abstract This simulation case centers on a patient who had presented with a reported overdose of Meprozine, when in fact the patient had taken an overdose of long-acting insulin and developed recurrent hypoglycemia. It highlights the need to be thorough in evaluating patients with mental status changes and potential overdoses. The simulation has been very effective in teaching students and residents general management principles of the overdose patient, and the approach to a patient with mental status changes. Many of the students and residents miss the hypoglycemia in favor of performing unnecessary tests such as CT scanning, and fail to readdress vital signs and hypoglycemia as an etiology of the change. The most difficult portion of the case is conveying the appearance of a dystonic reaction with the simulator. A distractor, such as having the performer evaluate a second case or piece of data, seems to help convey the change in appearance. This case helps reinforce general approach principles very well.